2011
DOI: 10.1111/j.1365-3040.2011.02314.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation–reduction and reactive oxygen species homeostasis in mutant plants with respiratory chain complex I dysfunction

Abstract: Mutations in a mitochondrial or nuclear gene encoding respiratory chain complex I subunits lead to decreased or a total absence of complex I activity. Plant mutants with altered or lost complex I activity adapt their respiratory metabolism by inducing alternative pathways of the respiratory chain and changing energy metabolism. Apparently, complex I is a crucial component of the oxidationreduction (redox) regulatory system in photosynthetic cells, and alternative NAD(P)H dehydrogenases of the mitochondrial ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 83 publications
(387 reference statements)
1
42
0
Order By: Relevance
“…Like ascorbate, glutathione is found predominantly in the reduced form in many compartments. Tissue GSSG contents often correlate with dormancy and cell death (224,225), though GSSG can accumulate to high concentration in leaves without causing cell death though this is associated with much decreased growth (341).…”
Section: F Glutathione In Plantsmentioning
confidence: 99%
“…Like ascorbate, glutathione is found predominantly in the reduced form in many compartments. Tissue GSSG contents often correlate with dormancy and cell death (224,225), though GSSG can accumulate to high concentration in leaves without causing cell death though this is associated with much decreased growth (341).…”
Section: F Glutathione In Plantsmentioning
confidence: 99%
“…Specific AOX gene family members are strongly induced at the transcript and protein level by complex III or complex IV dysfunction (167,361), suggesting that AOX expression is highly responsive to insufficient cytochrome pathway capacity downstream of the ubiquinone pool. However, AOX is also commonly induced by complex I dysfunction and by other disruptions in respiratory metabolism such as the inhibition of ATP synthase, uncoupling of the mETC, and inhibition of the TCA cycle (164,362). However, since some other studies reported no change in AOX levels in response to dramatic changes in the ETC (319), it would seem reasonable to conclude that the expression level of AOX is governed by multiple and complex signals from the mETC (359).…”
Section: The Metcmentioning
confidence: 99%
“…AOX has been suggested as the primary target of the retrograde signal from mitochondrial stress (Zarkovic et al, 2005;Rhoads and Subbaiah, 2007;Van Aken et al, 2009a, 2009b, and AOX1a is also found to be regulated by ABI4, which is involved in retrograde signaling from chloroplasts (Koussevitzky et al, 2007;Giraud et al, 2009). Recent articles comparing the transcriptomic responses of mitochondrial mutants or plants treated with ETC inhibitors (Schwarzländer et al, 2012), as well as comparisons of phenotypes of different respiratory complex I mutants (Juszczuk et al, 2012), also highlight the complexity of responses to different mitochondrial dysfunctions. Defining the cause of phenotypic differences between diverse mitochondrial mutants should provide insight into the proposed, but currently unknown, retrograde signaling mechanisms from mitochondria to the nucleus.…”
Section: Shot1 Is Required For Normal Mitochondrial Gene Regulation Amentioning
confidence: 99%